2004
DOI: 10.1007/s00127-004-0869-7
|View full text |Cite
|
Sign up to set email alerts
|

Work and mental health

Abstract: The research questions pertaining to mental health are varied and will determine what mental health issues are of interest and the models of work applicable. There need to be more longitudinal studies and consideration of factors which the worker brings to the workplace (psychosocial issues, personality traits), as well as interpersonal issues and consideration of systemic, organizational, political and economic factors, including leadership styles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 53 publications
2
44
0
3
Order By: Relevance
“…Moreover, in recent years, a multitude of studies has concluded that mental health is associated with working conditions and more particularly with psychosocial constraints at work. These constraints help to explain in part the differences observed according to occupational categories, although the specific proportion attributable to working conditions remains imprecise [Stansfeld et al, 1998[Stansfeld et al, , 1999Van der Doef et al, 1999;Tennant, 2001;Wilhelm et al, 2004;Ylipaavalniemi et al, 2005;Rugulies et al, 2006;Stansfeld and Candy, 2006].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, in recent years, a multitude of studies has concluded that mental health is associated with working conditions and more particularly with psychosocial constraints at work. These constraints help to explain in part the differences observed according to occupational categories, although the specific proportion attributable to working conditions remains imprecise [Stansfeld et al, 1998[Stansfeld et al, , 1999Van der Doef et al, 1999;Tennant, 2001;Wilhelm et al, 2004;Ylipaavalniemi et al, 2005;Rugulies et al, 2006;Stansfeld and Candy, 2006].…”
Section: Discussionmentioning
confidence: 97%
“…Since very few high-quality epidemiologic studies have been conducted on psychosocial work factors in France, we included studies from other industrialized countries in our literature review. As recent and updated literature reviews were available for the three health outcomes, we selected papers on the basis of literature reviews on CVD (Belkic et al 2004;De Lange et al 2003;Hemingway and Marmot 1999;Kasl 1996;Kivimäki et al 2006b;Kristensen 1995Kristensen , 1996Kuper et al 2002;Schnall et al 1994;Tennant 2000;Theorell and Karasek 1996;Van der Doef and Maes 1998), mental disorders (Bonde 2008;De Lange et al 2003;Michie and Williams 2003;Netterstrom et al 2008;Sanderson and Andrews 2006;Siegrist 2008;Stansfeld and Candy 2006;Tennant 2001;Van der Doef and Maes 1999;Wilhelm et al 2004) and MSD (Van der Doef and Maes 1998;De Lange et al 2003;Ariens et al 2001;Bongers et al 1993Bongers et al , 2002Bongers et al , 2006Burdorf and Sorock 1997;Davis and Heaney 2000;Ferguson and Marras 1997;Hales and Bernard 1996;Hartvigsen et al 2004;Hoogendoorn et al 2000;Linton 2000Linton , 2001Malchaire et al 2001;…”
Section: Relative Risk Estimatesmentioning
confidence: 99%
“…However, in many studies associations between psychosocial working conditions and mental health problems have been lacking or an association has been found in one gender only. Until recently, most studies examining the associations between working conditions and mental health have been cross-sectional [5,17]. Furthermore, nearly all studies have used self-reported measures of both working conditions and mental health.…”
Section: Introductionmentioning
confidence: 99%